2016
DOI: 10.15448/1983-652x.2016.3.24345
|View full text |Cite
|
Sign up to set email alerts
|

Uso de rastreadores para detecção de eventos adversos aos medicamentos em hospital universitário

Abstract: Objetivo: Identificar eventos adversos a medicamentos (EAM) em pacientes adultos internados nas clínicas médica e cirúrgica em um hospital universitário, bem como caracterizar esses eventos.Materiais e Métodos: Foi realizado estudo retrospectivo em um hospital universitário. A amostra foi constituída pelos prontuários dos pacientes internados nas clínicas médica e cirúrgica entre outubro de 2010 e janeiro de 2011. Para identificação dos EAM aplicou-se um conjunto de rastreadores que são condições que podem ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…A retrospective study, developed in a Brazilian university hospital based on the analysis of 263 medical records, identified that 58 patients had at least one ADE during their hospitalization period, which led to an incidence of 22.1%, with 83 distinct ADEs identified, resulting in a rate of 31.5 ADE per 100 patients (2) .…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective study, developed in a Brazilian university hospital based on the analysis of 263 medical records, identified that 58 patients had at least one ADE during their hospitalization period, which led to an incidence of 22.1%, with 83 distinct ADEs identified, resulting in a rate of 31.5 ADE per 100 patients (2) .…”
Section: Introductionmentioning
confidence: 99%